Induction of internal circadian desynchrony by misaligning zeitgebers - Isabel Heyde; Henrik Oster (Scientific Reports, 2022)
Abstract 24-h rhythms in physiology and behaviour are orchestrated by an endogenous circadian clock system. In mammals, these clocks are hierarchically organized with a master pacemaker residing in the hypothalamic suprachiasmatic nucleus (SCN). External time signals—so-called zeitgebers—align internal with geophysical time. During shift work, zeitgeber input conflicting with internal time induces circadian desynchrony which, in turn, promotes metabolic and psychiatric disorders. However, little is known about how internal desynchrony is expressed at the molecular level under chronodisruptive environmental conditions. We here investigated the effects of zeitgeber misalignment on circadian molecular organisation by combining 28-h light–dark (LD-28) cycles with either 24-h (FF-24) or 28-h feeding-fasting (FF-28) regimes in mice. We found that FF cycles showed strong effects on peripheral clocks, while having little effect on centrally coordinated activity rhythms. Systemic, i.e., across-tissue internal circadian desynchrony was profoundly induced within four days in LD-28/FF-24, while phase coherence between tissue clocks was maintained to a higher degree under LD-28/FF-28 conditions. In contrast, temporal coordination of clock gene activity across tissues was reduced under LD-28/FF-28 conditions compared to LD-28/FF-24. These results indicate that timed food intake may improve internal synchrony under disruptive zeitgeber conditions but may, at the same time, weaken clock function at the tissue level.